Revealing Corporate Value: The Role of Investment Decisions, Debt Policy, and Ownership Structure - Ida Ayu Sri Brahmayanti (JASF: Journal of Accounting and Strategic Finance, 2024)
This study examines how investment decisions, debt strategies, and ownership structures influence corporate value, specifically targeting manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2021. Using a quantitative approach and Partial Least Squares (PLS), the research integrates these critical factors into a comprehensive framework. The findings indicate that asset growth significantly impacts corporate value, highlighting the importance of effective investment strategies, while debt expansion positively influences firm value. However, managerial ownership does not exhibit a strong direct relationship with asset growth, equity expansion, or debt policies. Furthermore, this study highlights the significant role of institutional investors in strengthening corporate governance and reducing agency conflicts. Drawing on recent findings, it underscores the importance of intellectual capital and cash reserves in boosting financial performance and market valuation. The effective management of intellectual capital components—namely human, structural, and relational capital—serves as a bridge between financial performance and market valuation, while strategic cash reserves reflect financial stability and potential for growth. By synthesizing investment, financing, and ownership decisions, this study offers a novel perspective and practical implications for firms navigating post-pandemic economic recovery, emphasizing the synergy of financial strategies in optimizing corporate value and enhancing shareholder wealth.